Assessment big data in Nigeria: Identification, generation and processing in the opinion of the experts - Nkechi Patricia-Mary Esomonu; Martins Ndibem Esomonu; Lydia Ijeoma Eleje (Institute of Advanced Engineering and Science, 2020)
As a result of increasing complexity of assessing all aspects of human behaviours, a lot of data are generated on individual learner and from teachers and the system. What qualifies as big data in assessment in Nigeria? This research identifies the sources of assessment big data in Nigeria, investigates how the big data are generated and processed, and identifies the problems of generating and processing assessment big data in Nigeria. Through purposive sampling technique forty-five experts in education assessment and research were selected. The instruments for data collection were interview and documents. The data collected were analysed using descriptive statistics to answer the five research questions that guided the research. The results of the investigation showed that the internal and external examinations and assessments from secondary schools, and course work results in universities were identified by more than 95.5% of the experts interviewed as the major sources of assessment data in Nigeria. The major problem in generating and processing assessment big data from the experts’ opinions is low awareness on the need/advantages of assessment big data with the highest mean rating (4.29±0.76). Many data are not analysed and a lot of information are lost. Recommendation was made amongst others on the need for the stakeholders to create awareness on the importance of big data in the modern education system to improve learner’s performance.